Meteorological data from Feresjön, floating platform, 2021-04-28–2021-10-26 - Asa Research Station (Swedish University of Agricultural Sciences, 2025)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Asa Research Station (2025). Meteorological data from Feresjön, floating platform, 2021-04-28–2021-10-26 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/yY13bavmwXArzmeDAv58qiTn
Keywords: Asa Research Station; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Wind speed; Wind speed; Air temperature; Air temperature; Relative humidity; Relative humidity; Photosynthetically active radiation; Photosynthetically active radiation; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap